Incidence and lifetime costs of injuries in the United States - Corso, P.; Finkelstein, E.; Miller, Ted; Fiebelkorn, I.; Zaloshnja, E. (B M J Group, 2015)
© 2015, BMJ. All rights reserved. Background Standardized methodologies for assessing economic burden of injury at the national or international level do not exist. Objective To measure national incidence, medical costs, and productivity losses of medically treated injuries using the most recent data available in the United States, as a case study for similarly developed countries undertaking economic burden analyses. Method The authors combined several data sets to estimate the incidence of fatal and non-fatal injuries in 2000. They computed unit medical and productivity costs and multiplied these costs by corresponding incidence estimates to yield total lifetime costs of injuries occurring in 2000. Main outcome measures Incidence, medical costs, productivity losses, and total costs for injuries stratified by age group, sex, and mechanism. Results More than 50 million Americans experienced a medically treated injury in 2000, resulting in lifetime costs of $406 billion; $80 billion for medical treatment and $326 billion for lost productivity. Males had a 20% higher rate of injury than females. Injuries resulting from falls or being struck by/against an object accounted for more than 44% of injuries. The rate of medically treated injuries declined by 15% from 1985 to 2000 in the US. For those aged 0–44, the incidence rate of injuries declined by more than 20%; while persons aged 75 and older experienced a 20% increase. Conclusions These national burden estimates provide unequivocal evidence of the large health and financial burden of injuries. This study can serve as a template for other countries or be used in intercountry comparisons.